Предмет: Алгебра,
автор: Аноним
помогите решить пожалуйста,с решением
Приложения:
Ответы
Автор ответа:
0
x + 21/(x-3)(x+3)=x/(x-3)
x + 21 - x(x-3)/(x -3)(x+3)= 0
x + 21 - x² + 3x = 0; x ≠ 3; x ≠ - 3
-x² + 4x + 21 = 0
x² - 4x - 21 = 0
x1 = 7 ; x2 = -3
x = 7
x + 21 - x(x-3)/(x -3)(x+3)= 0
x + 21 - x² + 3x = 0; x ≠ 3; x ≠ - 3
-x² + 4x + 21 = 0
x² - 4x - 21 = 0
x1 = 7 ; x2 = -3
x = 7
Автор ответа:
0
2x + y = 12; x² - y =
Автор ответа:
0
23. y = 12 - 2x x² - 12 + 2x = 23 x² + 2x - 35 = 0 x1 = -7 y1 = 26 x2= 5 y2 = 2
Автор ответа:
0
Ответ: (-7; 26); (5; 2)
Автор ответа:
0
с2. не знаю
Автор ответа:
0
.........................
Приложения:
Автор ответа:
0
ответ 7, потому что -3 не удовлетворяет одз
Похожие вопросы
Предмет: Английский язык,
автор: dunaevan2006
Предмет: Биология,
автор: masha56628
Предмет: История,
автор: c2768207
Предмет: Обществознание,
автор: aleksandraniko
Предмет: Математика,
автор: ВЛАД98